Carbon footprint reporting process and software assessment framework - Martinek-Jaguszewska, Klaudia (Journal of Management and Financial Sciences, 2025)
ESG reporting requirements are a response to global environmental and social challenges. Sustainability reporting poses challenge for organizations, mostly due to complex regulations and numerous calculation methods, causing confusion and requiring in-depth research and learning. This research is focused on carbon footprint reporting, indicating the role and importance of purpose-built reporting software in this process. The framework carbon footprint reporting process (F-CF-RP) was proposed based on a literature review, with the aim of providing guidance and indicating the steps required for proper CF reporting. Based on the guidelines, standards, literature and software review, the carbon footprint reporting software assessment framework (CF-RS-AF) was developed to provide researchers and practitioners with a framework to systematize the selection process of carbon footprint reporting software. The framework combines functional and non-functional requirements, support and pricing models, and automated and artificial intelligence functionalities. The framework was positively validated with review of sample tools.